Dignity Therapy: A feasibility study of elders in long-term care. - Chochinov, H.; Cann, B.; Cullihall, K.; Kristjanson, Linda; Harlos, M.; McClement, S.; Hack, T.; Hassard, T. (Cambridge University Press, 2012)
Objective: The purpose of this study was to assess the feasibility of dignity therapy for the frail elderly. Method: Participants were recruited from personal care units contained within a large rehabilitation and long-term care facility in Winnipeg, Manitoba. Two groups of participants were identified; residents who were cognitively able to directly take part in dignity therapy, and residents who, because of cognitive impairment, required that family member(s) take part in dignity therapy on their behalf. Qualitative and quantitative methods were applied in determining responses to dignity therapy from direct participants, proxy participants, and healthcare providers (HCPs). Results: Twelve cognitively intact residents completed dignity therapy; 11 cognitively impaired residents were represented in the study by way of family member proxies. The majority of cognitively intact residents found dignity therapy to be helpful; the majority of proxy participants indicated that dignity therapy would be helpful to them and their families. In both groups, HCPs reported the benefits of dignity therapy in terms of changing the way they perceived the resident, teaching them things about the resident they did not previously know; the vast majority indicated that they would recommend it for other residents and their families.Significance of results: This study introduces evidence that dignity therapy has a role to play among the frail elderly. It also suggests that whether residents take part directly or by way of family proxies, the acquired benefits—and the effects on healthcare staff—make this area one meriting further study.